2002
DOI: 10.1093/jn/131.10.3061
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Effect of the Acute Phase Response on Indicators of Micronutrient Status in Indonesian Infants

Abstract: Many indicators of micronutrient status change during infection because of the acute phase response. In this study, relationships between the acute phase response, assessed by measuring concentrations of C-reactive protein (CRP), alpha(1)-antichymotrypsin (ACT) and alpha(1)-acid glycoprotein (AGP), and indicators of micronutrient status were analyzed in 418 infants who completed a 6-mo randomized, double-blind, placebo-controlled, supplementation trial with iron, zinc and/or beta-carotene. The acute phase resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
4
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 23 publications
14
141
4
7
Order By: Relevance
“…Plasma concentrations of retinol and zinc fall, and those of ferritin rise during an acute-phase reaction, and thus these indicators may not reliably reflect micronutrient status in the presence of inflammation (Wieringa et al, 2002). As clinical examination can often not exclude the presence of minor or low-grade chronic infection, seven infants with an acute-phase response, as indicated by a plasma CRP concentration 410 mg/ l, were excluded from the statistical analyses of micronutrient indicators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentrations of retinol and zinc fall, and those of ferritin rise during an acute-phase reaction, and thus these indicators may not reliably reflect micronutrient status in the presence of inflammation (Wieringa et al, 2002). As clinical examination can often not exclude the presence of minor or low-grade chronic infection, seven infants with an acute-phase response, as indicated by a plasma CRP concentration 410 mg/ l, were excluded from the statistical analyses of micronutrient indicators.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the present study are in line with the results of Jason et al (2001), who reported that vitamin A-deficient children had a relative type-1 cytokine dominance with significantly more T cells producing IFN-g, and less macrophages producing interleukin-10. Unfortunately, only clinical markers of acute infection were including in the study by Jason et al, which might not be specific enough to exclude an acute-phase response (Wieringa et al, 2002). Furthermore, 25% of the infants had HIV infection, making interpretation of the effects of vitamin A deficiency on immune function more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…It is of course possible that factors such as subclinical inflammation may impact on the measurement of biological indices of zinc (Brown, 1998;Wieringa et al, 2002;Duggan et al, 2005), and other nutrients may have had secondary effects on immune function in our study volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…4 The level of subclinical inflammation will depend on exposure to infection, sanitation, health facilities etc. In apparently healthy Indonesian infants Wieringer et al 50 found that 44% had elevated serum CRP and AGP concentrations. Panter-Brick et al 73 reported that stunting was significantly associated with high plasma ACT concentrations in Nepali village children.…”
Section: Inflammation In Subjects In Developing Countriesmentioning
confidence: 98%
“…Other workers have shown elevated acute-phase proteins in apparently healthy Indonesian children in this region. 50 In fact, the recruits in this study were selected on the basis of having a low haemoglobin concentration. Selection of such people is most likely to recruit persons with elevated acute-phase proteins 4,51,52 as these people are likely to have had the highest or most frequent exposure to disease impairing their ability to mobilise iron to synthesise haemoglobin.…”
Section: Anaemic Lactating Women In West Java Indonesiamentioning
confidence: 99%